An Analysis of Prejudice in Tayari Jones’s Novel An American Marriage - Ambarwati, Widi; Nasution, Siti Norma (Center of Language and Cultural Studies [CLCS], 2021)
In this study, the researchers analyze the forms of prejudice namely stereotype, social distance, and discrimination. This study aims to reveal that literary works reflect social reality. The object of this study is a novel entitled